One Village One Brand for Sustainable Rural Economic Development: A Three Stream Perspective - Nurul Azizah; Arimurti Kriswibowo (Jurnal Wilayah dan Lingkungan, 2020)
Brand is the concrete form to encourage the intellectual property right (IPR) awareness. IPR becomes key to promote the product abroad. However, there is still a little awareness about how to protect the IPR, in the rural business area particularly. Thus, it becomes necessary to create a brand in a village, which will cover all the rural masterpieces to encourage the rural economy and protect its potential. This strategy is called as one village one brand. OVOB “One Village One Brand” is initiated by APEC project of Korea Institute of intellectual property and this program supports the economic growth and development in the Asia Pacific region. This study focused on the Agenda Setting stage. This study aims to find out how the Agenda Setting process of One Village One brand (OVOB) program in Kediri Regency. This research uses descriptive-qualitative approach with data collection techniques in the form of literature review, observation, and documentation. The result found that the BUMDES “Karya Mandiri” OVOB Program Setting Agenda uses the Quick Decision Analysis method. Meanwhile, the Public Problem Priority Preparation Technique is used through the priority process of public problems, evaluating by stakeholders on policy alternatives, and inferring priority issues. The Agenda Setting process correspond to Three Stream Theory, that is, in terms of the Problem Stream, it is known that problem mapping is done by the rural government. By the Policy Stream, the single-issue background is the issue of lack of skills and infrastructure which is then reviewed and produces the OVOB program. According to Politics Stream, this program will get support from the village government and the budget is included in the APBD that supports what is then included in the village government work program and BUMDES.